Conditions of obtaining porous carbon materials from pyrolyzed wood wastes by chemical activation of H3PO4 - Zubkova, Valentyna; Shendrik, Tatiana; Kuzmin, Oleg (My University, 2017)
The purpose of this publication is to search for alternative materials – food industry wastes; valuation of it’s use in the production of porous carbon materials for use in water treatment systems.
Keywords: піроліз; відхід; активація; нанопора; адсорбент; пиролиз; отход; активация; нанопора; адсорбент; pyrolysis; waste; activation; nanopore; adsorbent; кафедра технології ресторанної і аюрведичної продукції